Fundamentalisms observed - Marty, Martin E.; Appleby, R. Scott (The fundamentalism project, 1991)
North American protestant fundamentalism / Nancy T. Ammerman -- Roman Catholic traditionalism and activist conservatism in the United States / William D. Dinges and James Hitchcock -- Protestant fundamentalism in Latin America / Pablo A. Deiros -- Religious fundamentalism and religious Jews : the case of the Haredim / Samuel C. Heilman and Menachem Friedman -- Jewish Zionist fundamentalism : the bloc of the faithful in Israel (Gush Emunim) / Gideon Aran -- Fundamentalism in the Sunni Arab World : Egypt and the Sudan / John O. Voll -- Activist Shi∫αism in Iran, Iraq, and Lebanon / Abdulaziz A. Sachedina